2021
DOI: 10.3390/math9233122
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Stochastic Modeling of COVID-19 with Environmental Noise from the Analytical and Numerical Point of View

Abstract: In this article, we propose a novel mathematical model for the spread of COVID-19 involving environmental white noise. The new stochastic model was studied for the existence and persistence of the disease, as well as the extinction of the disease. We noticed that the existence and extinction of the disease are dependent on R0 (the reproduction number). Then, a numerical scheme was developed for the computational analysis of the model; with the existing values of the parameters in the literature, we obtained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Mathematical models are variedly used as a significant tool in understanding natural phenomena (Hussain, Madi, Iqbal, et al, 2021). Namely, the stochastic epidemic model was utilized to predict the COVID-19 spread (Hussain, Madi, Khan, et al, 2021).…”
Section: Agglomerative Hierarchical Clusteringmentioning
confidence: 99%
“…Mathematical models are variedly used as a significant tool in understanding natural phenomena (Hussain, Madi, Iqbal, et al, 2021). Namely, the stochastic epidemic model was utilized to predict the COVID-19 spread (Hussain, Madi, Khan, et al, 2021).…”
Section: Agglomerative Hierarchical Clusteringmentioning
confidence: 99%
“…They have considered the CTMC stochastic model and found that disease may not persist even for basic reproduction number ( ) greater than one. Hussain et al [ 28 ] have proposed the deterministic model along with stochastic differential equation model involving environmental white noise. They analyzed the deterministic model and compared the results of stochastic and deterministic models for the future prediction of the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the Ulam-Hyers stability (UHS) has attracted the attention of many authors according to their applications in mechanic, automatic, biology, and fluid flow, where identifying the explicit solutions is a hard task. Many research articles have been appeared in this field; like for qualitative study of fractional stochastic systems, see earlier studies [9][10][11][12][13][14][15], and for applications to Stochastic Epidemic SIR Model, the COVID-19, Volterra integro-differential system, and tobacco smoking model, see other research [16][17][18][19]. Guo et al [13] have investigated the EU and UHS of solutions for almost periodic stochastic differential equations with fBm.…”
Section: Introductionmentioning
confidence: 99%